2018
DOI: 10.1684/epd.2018.0992
|View full text |Cite
|
Sign up to set email alerts
|

Electroclinical history of a five‐year‐old girl with GRIN1‐related early‐onset epileptic encephalopathy: a video‐case study

Abstract: De novo mutations in the GRIN1 gene have been recently reported as the molecular cause of a broad-spectrum early-onset neurological phenotype. Here, we describe a five-year-old girl with an early-onset epileptic encephalopathy associated with an infantile hyperkinetic movement disorder and oculomotor abnormalities. Whole-exome sequencing identified a novel p.Met641Leu de novo variant in the GRIN1 gene as the cause of the phenotype. In silico analysis suggested that the p.Met641Leu variant would alter the gatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The hyperkinetic movements in our proband were gradually ameliorated after the seizures subsided, and they were minimal at 23 months of age. In a single case reported by Pironiti et al [13], abnormal movements were observed evidently during infancy and less prominently at five years of age. Data regarding the prognosis of movement disorders are limited.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The hyperkinetic movements in our proband were gradually ameliorated after the seizures subsided, and they were minimal at 23 months of age. In a single case reported by Pironiti et al [13], abnormal movements were observed evidently during infancy and less prominently at five years of age. Data regarding the prognosis of movement disorders are limited.…”
Section: Discussionmentioning
confidence: 83%
“…Concerning the genotype-phenotype correlation, the GRIN1 mutations in the patients with extensive bilateral polymicrogyria have been found to be located in M3 or S2, with the patients exhibiting severe phenotypes, including intractable epilepsy, cortical blindness, microcephaly, profound delay, and spastic tetraplegia [11,12]. Heterozygous de novo mutations have been reported in most patients with GRIN1-NDHMS; however, homozygous mutations have also been detected in some patients [5][6][7][8][9][10][11][12][13][14]. Most GRIN1 mutations result in a loss of function [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 PLA2G6 associated neurodegeneration (PLAN), which occurs due to a homozygous mutation of PLA2G6, is a rare cause of OGC. 20 Some neurodegenerative disorders are also found to be associated with the occurrence of OGC, such as mutations in the GRIN1 gene, which affects the function of both N-methyl-D-aspartate and dopamine D1 receptors, leading to oculomotor dystonic reactions; 21,22 Neuronal intranuclear hyaline inclusion disease, a multisystem degenerative disorder that involves both central and peripheral nervous systems, causing diffuse muscle spasms, dysarthria, dysphagia, tremors, ataxia, OGC, progressive muscle weakness, and atrophy 23 ; Rett syndrome, progressive neurodegenerative disorder in females, leads to gait disturbance, bruxism, OGC, parkinsonism, and dystonia 24 and tyrosine hydroxylase (TOH) deficiency, an inborn error of catecholamine biosynthesis causing dystonia along with tremor, hypersensitivity to levodopa therapy, OGC, akinesia, and rigidity. 25,26 Other autosomal recessive disorders that rarely present with OGC are Kufor Rakeb, 27 haemophagocytic lymphohistiocytosis, 28 sepiapterin reductase deficiency, 29,30 and GTP cyclohydrolase I deficiency.…”
Section: Etiology Of Ogcmentioning
confidence: 99%